2022
DOI: 10.1088/1612-202x/aca978
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of ultrashort single-pulse and multi-pulse driven laser wakefield acceleration

Abstract: Laser wakefield acceleration (LWFA) is a promising technique to build compact and powerful particle accelerators. In such accelerators, the electric fields required to accelerate charged particles are sustained by electron density modulations in the plasma. The plasma wave modulating the electron density may be excited by an intense laser pulse. However, propagation of intense laser pulse in plasma is subject to various instabilities which result in significant losses of laser energy, reducing the efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The super-Gaussian beams have been found to be a better candidate for the third harmonic generation [50]. Not only this, studies have shown significant impact of the laser intensity profile and laser parameters on the amplitude of the wakefield [51] generated during the propagation of laser pulses and trapping of high-quality electron bunch in the bubble [52]. These laser beams, when skewed or launched as such, have also been found to be superior in other areas of optics also [53][54][55].…”
Section: General Treatment For Super-gaussian Beammentioning
confidence: 99%
“…The super-Gaussian beams have been found to be a better candidate for the third harmonic generation [50]. Not only this, studies have shown significant impact of the laser intensity profile and laser parameters on the amplitude of the wakefield [51] generated during the propagation of laser pulses and trapping of high-quality electron bunch in the bubble [52]. These laser beams, when skewed or launched as such, have also been found to be superior in other areas of optics also [53][54][55].…”
Section: General Treatment For Super-gaussian Beammentioning
confidence: 99%
“…These electrons are then trapped in the first wake at the tail of the bubble and can be self-injected into the bubble [11][12][13][14][15][16][17][18][19][20]. Selfinjection of plasma electrons in bubble wakefield is the development for generation of high quality electrons beam [21][22][23][24][25][26][27][28][29][30]. These high quality electron beams are being used for many applications such as material characterization [31], generation of synchrotron radiations such as betatron radiations, and these radiations have been used in medical treatments [32][33][34][35][36][37] and many more [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%